Kualitas Pelayanan Publik Bagi Penyandang Disabilitas di Mal Pelayanan Publik Kota Pekanbaru - Sintya Trifira; Roni Ekha Putera; Yoserizal Yoserizal (Journal of Social and Policy Issues, 2022)
This research aims to describe the quality of public services for people with disabilities at the Pekanbaru Public Service Mall meanwhile, a lot of people with disabilities who experience discrimination related to the fulfillment of their rights in public services. So, it is necessary to assess the quality of public services that have been provided to persons with disabilities. Pekanbaru Public Service Mall is one of the places for integrated public services, there are various kinds of government and private agencies that provide public services. With a high number of visits per day, Pekanbaru Public Service Mall is expected to be the answer for people with disabilities to use public services more efficiently, easily, comfortably and safely. This reaserch is a quality research with using interviews, observation and documentation as a method to collect the data. The results of this study indicate that the quality of service at the Pekanbaru City Public Service Mall is very good. Persons with disabilities feel very cared about for their service needs and accessibility. Although there are still shortcomings in the facilities provided, the Pekanbaru Public Service Mall has tried to provide the best service for the people with disabilities. It is proven based on the results of research that people with disabilities feel efficiency, responsiveness and there is no difference between people with disabilities and other communities. To provide better public services, service officers should be given special education and training for persons with disabilities, and always maintain the facilities for persons with disabilities that have been provided.